2021
DOI: 10.1038/s41598-021-97353-w
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the enhanced Nb3Sn performance by combined Hf and Ta doping

Abstract: In recent years there has been an increasing effort in improving the performance of Nb3Sn for high-field applications, in particular for the fabrication of conductors suitable for the realization of the Future Circular Collider (FCC) at CERN. This challenging task has led to the investigation of new routes to advance the high-field pinning properties, the irreversibility and the upper critical fields (HIrr and Hc2, respectively). The effect of hafnium addition to the standard Nb-4Ta alloy has been recently dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…At higher magnifications, brighter dots were observed on the exposed grains, as shown in figure 4. Based on previous observations and analyses [26,35,36], these dots are likely oxide nanoprecipitates (HfO 2 or ZrO 2 , depending on the third element added to the Nb alloy). Currently we are not able to determine the composition or exact size of these particles.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…At higher magnifications, brighter dots were observed on the exposed grains, as shown in figure 4. Based on previous observations and analyses [26,35,36], these dots are likely oxide nanoprecipitates (HfO 2 or ZrO 2 , depending on the third element added to the Nb alloy). Currently we are not able to determine the composition or exact size of these particles.…”
Section: Resultsmentioning
confidence: 85%
“…They appear nevertheless to confirm a lower size for the HfO 2 precipitates. Based on atomic probe tomography, Tarantini et al [36] reported HfO 2 precipitate sizes of approximately 3 nm and Nb 3 Sn grains below 70 nm (between 55 and 68 nm) in a wire manufactured by Balachandran et al [22] and reacted at 670 • C. Ortino et al [40] measured by transmission electron microscopy ZrO 2 precipitates of 4.6 nm and Nb 3 Sn grain sizes of 70 nm in APC-PIT reacted at 675 • C. This comparison based on literature data and our own results in this paper is unfortunately not sufficient to fully understand how the size and distribution of oxides precipitate affect the grain refinement. Moreover, the variation of the size distributions of the Nb 3 Sn grain across the reacted layer have rarely been systematically studied.…”
mentioning
confidence: 99%
“…Although the calculated example above is an extreme case, the importance of a small grain-size was already recognized in the 1990's [22][23][24], while its impact on the pinningcurve was demonstrated later [19]. Attempts to evoke smaller grain-sizes and/or introduce artificial pinning centers in wires have only recently become successful [25], and this triggered active current research into this way to further optimize Nb 3 Sn [26][27][28][29][30][31]. planes as a result of [100] strain, and the resulting reduction in the electron density-of-states if the sub-lattice distortion is either allowed or suppressed.…”
Section: Optimizing Pinningmentioning
confidence: 99%
“…The first report of APT analysis on Nb 3 Sn wires in 2013 [10] showed grain boundary segregation of Cu and Ti, quantified using the principle of Gibbsian excess at grain boundaries. More recently APT has been used to look at the size distribution and number density of nanoscale HfO 2 and ZrO 2 pinning centres in Nb 3 Sn [24,25] and to investigate the concentrations of species at the Nb/Nb 3 Sn interface in an internally oxidised Nb 3 Sn wire doped with Zr and O [26]. However APT analysis has not yet been applied to the characterisation of commercial RRP ® wires nor any form of irradiated Nb 3 Sn wires.…”
Section: Introductionmentioning
confidence: 99%